Sensation seeking as a potential screening tool for suicidality in adolescence. (December 2015) - Lee, Won; Lim, Dohee; Lee, Hye; Park, Hyesook
Abstract Background Although suicide could be an adverse health problem related to sensation seeking, this relationship has not been rigorously evaluated. The purpose of this study was to evaluate the relationship between sensation seeking and suicidality (suicidal ideation and plan) among adolescents and to test the influence of depressive symptom on this relationship. Methods We surveyed 2, 017 adolescents in seven middle and high schools located in urban and rural areas in 2012. A self-report questionnaire included items about demographic characteristics, sensation seeking, depressive symptom, and suicide plans. We evaluated the influence of sensation seeking on suicide plan using multiple logistic regression and causal mediation analysis. Results Sensation seeking was related to suicide ideation and plan. Sensation seeking was associated with a 13 % greater likelihood of a suicide plan during the past 12 months as the score increased by 1. After controlling for depressive symptom, the effect of sensation seeking was reduced, but still significantly increased the risk (adjusted odds ratio: 1.10; 95 % CI: 1.04–1.16). When depressive symptom was included as a potential mediator, depressive symptom exerted an indirect effect on suicide planning that constituted 37 % of the total effect of sensation seeking. There was no significant interaction between sensation seeking and either demographic variables or depressive symptom. Conclusions Sensation seeking can contribute to developing a suicide plan directly and indirectly via depressive symptom. Sensation seeking could be used to identify high-risk adolescents and provide proper interventions.